QTL mapping and stability analysis of trichome density in zucchini (Cucurbita pepo L.) - Wang, Yunli; Wang, Guichao; Lin, Dongjuan; Luo, Qinfen; Xu, Wenlong; Qu, Shuping (Frontiers in Plant Science, 2023)
Trichomes provide an excellent model for studying cell differentiation and proliferation. The aboveground tissues of plants with long dense trichomes (LDTs) can cause skin itching in people working in a zucchini field, in which management, pollination and fruit harvesting are difficult. In this study, an F2 population was constructed with LDT inbred line '16' and sparse micro trichome (SMT) inbred line '63' for QTL analysis of type I and II trichome density. Two QTLs were identified on chromosomes 3 and 15 using the QTL-seq method. Additionally, 191 InDel markers were developed on 20 chromosomes, a genetic map was constructed for QTL mapping, and three QTLs were identified on chromosomes 3, 6 and 15. Two QTLs, CpTD3.1 and CpTD15.1, were identified in both QTL-seq and genetic map-based QTL analyses, and CpTD15.1 was the major-effect QTL. The stability of CpTD3.1 and CpTD15.1 was confirmed using data from F2 plants under different environmental conditions. The major-effect QTL CpTD15.1 was located between markers chr15-4991349 and chr15-5766791, with a physical distance of 775.44 kb, and explained 12.71-29.37% of the phenotypic variation observed in the three environments. CpTD3.1 was located between markers chr3-218350 and chr3-2891236, in a region with a physical distance of 2672.89 kb, and explained 5.00-10.64% of the phenotypic variation observed in the three environments. The functional annotations of the genes within the CpTD15.1 region were predicted, and five genes encoding transcription factors regulating trichome development were selected. Cp4.1LG15g04400 encoded zinc finger protein (ZFP) and harboured nonsynonymous SNPs in the conserved ring finger domain between the two parental lines. There were significant differences in Cp4.1LG15g04400 expression between '16' and '63', and a similar pattern was found between germplasm resources of LDT lines and SMT lines. It was presumed that Cp4.1LG15g04400 might regulate trichome density in zucchini. These results lay a foundation for better understanding the density of multicellular nonglandular trichomes and the regulatory mechanism of trichome density in zucchini.